First, simplify both sides of the equation:
4x + 3(x - 2) = 8x - (6 + x)
4x + 3x - 6 = 8x - 6 - x
7x - 6 = 7x - 6
Now, notice that the equation simplifies to -6 = -6. This equation is always true, which means that the solution is infinite. Thus, the correct answer is "infinite solutions".
What is the solution to the equation below?
4x+3(x−2)=8x−(6+x)
This problem requires you to show your work.
(1 point)
Responses
no solution
no solution
x=−4
x is equal to negative 4
x=6
x is equal to 6
infinite solutions
1 answer